2002
DOI: 10.1002/ptr.1024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acanthopanax senticosus Harms on biogenic monoamine levels in the rat brain

Abstract: The extract of the stem bark of Acanthopanax senticosus Harms (ASH) is known to have healing and protective effects on stress-induced disturbance of mental status. We have analysed whether a single or chronic (2 week) administration of ASH can affect concentrations of noradrenaline (NA), dopamine (DA) and their metabolites in the normal rat brain. A single p.o. administration of ASH elevated the NA and DA levels in the whole brain of rats in a dose-dependent manner. A single or 2 week administration of ASH (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 12 publications
(15 reference statements)
3
17
0
1
Order By: Relevance
“…We have confirmed that ASH increases NA and its turnover, especially in the anterior hypothalamus, 5,9) but alone it did not cause development of gastric erosions. This is clear from the results of a separate experiment in which we measured the gastric erosion index (GEI) to restraint stress (RS) in eight rats per treatment: ASH alone (0), water alone (0), water + RS (56:25 AE 3:82), and ASH + RS (23:75 AE 3:84).…”
supporting
confidence: 69%
“…We have confirmed that ASH increases NA and its turnover, especially in the anterior hypothalamus, 5,9) but alone it did not cause development of gastric erosions. This is clear from the results of a separate experiment in which we measured the gastric erosion index (GEI) to restraint stress (RS) in eight rats per treatment: ASH alone (0), water alone (0), water + RS (56:25 AE 3:82), and ASH + RS (23:75 AE 3:84).…”
supporting
confidence: 69%
“…Some reviews have been reported regarding the active substances and pharmacological effects of Eleutherococcus senticosus (Frasnsworth et al, 1985;Davydov and Krikorian, 2000;Deyama et al, 2001). Fujikawa et al (2002) reported that the oral administration of the extracts of Eleutherococcus senticosus for 2 weeks preferentially acted on the frontal cortex and anterior hypothalamus of rats to enhance the noradrenaline level and its turnover, and further the long-term administration of their extracts stimulated dopamine and its turnover in the striatum and anterior hypothalamus. They suggested that the effects of Eleutherococcus senticosus extract on the noradrenaline and dopamine may be useful in the prevention of some stress-related diseases.…”
Section: Introductionmentioning
confidence: 98%
“…Further investigation using the stem bark of ASH has demonstrated that chlorogenic acid (CHA) and syringaresinol di-o-␤-d-glucoside (SYG), which are major components of the n-butanol extract prepared from ASH, markedly prevent the development of gastric ulcers in rats subjected to restraint stress in water (RSW) for 7 h (Fujikawa et al, 1996). ASH likely has both peripheral action and direct action on the brain, since oral administration of ASH affected the levels of dopamine (DA) and noradrenaline (NA) in the whole brain or dissected brain tissues of rats 30 min after administration (Fujikawa et al, 2002). The action was concentrated in areas that are related to PD such as the nigrostriatal DAergic system and stress sensitive areas such as the hypothalamus.…”
Section: Introductionmentioning
confidence: 99%